Effectiveness of formalised therapy for adolescents with cannabis dependence: A randomised trial. (2nd September 2016) - Lascaux, M.; Ionescu, S.; Phan, O.
Abstract: Aims : During the past 20 years, cannabis consumption among adolescents has dramatically increased. In France, over 300 outpatient treatment centres caring for youngsters with cannabis abuse diagnoses were created. For this study, five European countries participated in a randomised controlled trial on adolescents with cannabis addiction. The goal was to compare a Multidimensional Family Therapy (MDFT) to what was usually done in these five countries ("Treatment As Usual (TAU)"). In France, clinical practices are heterogeneous; therefore, the French TAU had to be formalised. French researchers compared MDFT to a formalised TAU and non-formalised one. The aim of this article is to present the interest of formalising therapeutic French practices. Methods : The efficacy of formalised versus unformalised therapy was assessed using two criteria: decrease of cannabis use over a one-year period measured by Adolescent Diagnostic Interview-light (ADI-light) and by Time Line Follow BACK (TLFB). Findings : Results show that the formalised therapy is more effective in preventing cannabis abuse than non-formalised therapy. At 12 months, this difference is statistically significant (TLFB: p  < 0.05). Conclusion : The formalisation of explicit TAU has strengthened the therapist's involvement in the therapeutic process. This study presents experimental results which demonstrate that formalisation and supervision increased therapeutic efficacy in the treatment of adolescents suffering from cannabis abuse or dependence.